Economic Potential of Traditional Cultural Expression From The Perspective of Indonesia’s Intellectual Property Righs Law - Stevanny, Stevanny; Gunawan Djajaputra (Dinasti Research, 2024)
Folk Songs are very vulnerable to be claimed by other parties, changed and/or re-sung inappropriately or deviating from the values ??of the traditional community. So it is important to conduct a research related to the protection of Folk Songs within the scope of Copyright Law in Indonesia.This research aims to gain knowledge by analyzing the regulation of Folk Songs in terms of Intellectual Property Law, especially Copyright and certainty regarding their commercial use which produces economic benefits. This study employs normative legal research techniques utilizing both conceptual and statutory approaches to comprehend legal facets through relevant literature and regulations. In accordance with the Explanation of Article 38 paragraph (1) of Law Number 28 of 2018 concerning Copyright, which states that the State holds creative rights and that other parties can implement copyright with permission from the creator or copyright holder in the form of a license agreement, this research shows that folk songs are one of the traditional cultural expressions. The Minister is authorized to execute license agreements on behalf of the State with other entities having a similar standing. Despite the issuance of Government Regulation Number 56 of 20222 concerning Communal Intellectual Property to carry out the mandate of Article 38 paragraph (4) Law Number 28 of 2018 concerning Copyright, the provisions regarding the procedures and implementation of this application have not been thoroughly regulated.